Correlations between gaze fixations to different areas of interest are related to tennis serve return performance in two different expert groups - Rosker, J.; Rosker, Z. M. (International Journal of Performance Analysis in Sport, 2021)
Interceptive tasks, such as returning a tennis serve, require efficient use of visual information. The aim of this study was to investigate whether there are differences in the gaze behaviour in two different groups of tennis players. Additionally, analysis between tennis serve returns of different quality have been conducted. Six-hundred and seventy-five returns performed by ten national and five international level tennis players were analysed. Focal visual attention was measured on-court using a mobile eye-movement tracking device. Fixations were mapped to different areas of interest relative to five consecutive service phases. Differences in the duration of visual fixations between different types of tennis returns were examined as well as correlations between most relevant areas of interest. Correlation analysis revealed differences in visual search strategies between both groups of tennis players. The international level group presented with gaze behaviour that indicates increased attention to specific visual information in tactically more successful serve returns. The national level tennis players on the other hand presented less specific gaze behaviour, and probably overall, less efficient attentional control. Additionally, international level tennis players presented return performance-specific gaze behaviour in the follow through-phase, which was not observed for the national level players.